2022
DOI: 10.1186/s12883-022-02586-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut- and oral-dysbiosis differentially impact spinal- and bulbar-onset ALS, predicting ALS severity and potentially determining the location of disease onset

Abstract: Background Prior studies on the role of gut-microbiome in Amyotrophic Lateral Sclerosis (ALS) pathogenesis have yielded conflicting results. We hypothesized that gut- and oral-microbiome may differentially impact two clinically-distinct ALS subtypes (spinal-onset ALS (sALS) vs. bulbar-onset ALS (bALS), driving disagreement in the field. Methods ALS patients diagnosed within 12 months and their spouses as healthy controls (n = 150 couples) were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 92 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…Changes in these factors included those regulated by NFkB, a known target of TauCl produced by the metabolism of NP001. Once LPS is removed as a perpetual driver of MT signaling, LPS reactive factors such as hepatocyte growth factor (HGF), neopterin, LPS-binding protein (LBP), IL-18 and epidermal growth factor (EGF) are up and down regulated relatively quickly [ 33 , 34 , 35 , 36 ]. The removal of CNS disease-associated activation signaling causes a decrease in monocyte migration into the CNS, which is reflected by decreased levels of soluble CD163 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these factors included those regulated by NFkB, a known target of TauCl produced by the metabolism of NP001. Once LPS is removed as a perpetual driver of MT signaling, LPS reactive factors such as hepatocyte growth factor (HGF), neopterin, LPS-binding protein (LBP), IL-18 and epidermal growth factor (EGF) are up and down regulated relatively quickly [ 33 , 34 , 35 , 36 ]. The removal of CNS disease-associated activation signaling causes a decrease in monocyte migration into the CNS, which is reflected by decreased levels of soluble CD163 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modifications in the composition of gut microbiota with a number of pathological microorganisms might play a crucial role in the pathogenesis of several diseases. Consistently, growing evidence has also linked gut dysbiosis to the exacerbation of compromised autophagy in certain inflammations [ 114 ]. Remarkably, metformin, a pleiotropic drug that is capable of modulating autophagy, could modify the metabolic process of gut microbiota [ 115 ].…”
Section: Future Perspectivesmentioning
confidence: 88%
“…Amyotrophic Lateral Sclerosis is a neuromuscular disease due to the progressive death of motor neurons and muscle atrophy [ 64 ]. Compared to PD and AD, there is less research available on the impact of dysbiosis on ALS.…”
Section: Chronic Pain Conditionsmentioning
confidence: 99%
“…Animal studies have demonstrated the impact of dysbiosis on ALS, where a reduced content of butyrate-producing bacteria resulted in gut permeability [ 53 ]. Animal studies have demonstrated intestinal dysbiosis in rodents prior to ALS manifestation, where leaky gut was also present [ 64 ]. Furthermore, alleviating dysbiosis improved ALS progression with worsening dysbiosis associated with more severe clinical symptoms [ 64 ].…”
Section: Chronic Pain Conditionsmentioning
confidence: 99%